Antiviral therapy of chronic hepatitis B virus infections: is resistance still a challenge? - Zoulim, Fabien (Henry Stewart Talks, 2011)
Hepatitis B virus, Chronic hepatitis B, Interferon, Nucleoside analogs, Viral resistance, Treatment management
Archived at 2022/01/30